Hereditary Critical Ω-Compositional Formations - Vedernikov, V. A.; Koptyukh, D. G. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We present a solution of the Shemetkov problem (on the investigation of critical formations) for piecewise-compositional hereditary formations.